2013
DOI: 10.1177/0886260513505703
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Reported by Two Samples of Deaf Adults via a Computerized American Sign Language Survey

Abstract: A computerized sign language survey was administered to two large samples of deaf adults. Six questions regarding intimate partner violence (IPV) were included, querying lifetime and past-year experiences of emotional abuse, physical abuse, and forced sex. Comparison data were available from a telephone survey of local households. Deaf respondents reported high rates of emotional abuse and much higher rates of forced sex than general population respondents. Physical abuse rates were comparable between groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…However, our findings, paired with Schild and Dalenberg’s findings, suggest that Deaf individuals may be particularly vulnerable to experiences of physical assault compared to the general hearing population. Our finding is corroborated by recent literature, which has demonstrated disparate rates of partner-perpetrated physical assault and crime victimization among Deaf individuals (Anderson and Leigh 2011; Harrell 2011; Pollard et al 2014). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our findings, paired with Schild and Dalenberg’s findings, suggest that Deaf individuals may be particularly vulnerable to experiences of physical assault compared to the general hearing population. Our finding is corroborated by recent literature, which has demonstrated disparate rates of partner-perpetrated physical assault and crime victimization among Deaf individuals (Anderson and Leigh 2011; Harrell 2011; Pollard et al 2014). …”
Section: Discussionsupporting
confidence: 90%
“…Deaf 1 individuals report trauma at nearly twofold higher rates than hearing individuals, including experiences of child abuse, intimate partner violence, sexual assault, and crime victimization (Anderson and Leigh 2011; Francavillo 2009; Harrell 2011; Pollard et al 2014; Sebald 2008). Factors believed to contribute to their increased vulnerability to trauma include, but are not limited to, deprivation of early language development, conflict in the family over education and communication methods, poor/inappropriate parental involvement, low self-esteem, and social isolation (Ridgeway 1993), as well as significant barriers to accessing services in American Sign Language (ASL), which severely limits Deaf individuals’ options for escaping from abusive relationships or other unsafe situations (Nosek et al 2001).…”
mentioning
confidence: 99%
“…A study of 120 oral (speech-only) deaf children suggested that those children with the least developed language abilities had significantly more behavior problems than their hearing peers [68]. Elevated rates of emotional problems and disorders [33] and interpersonal trauma exposure [31,32,34,57] are present, and may have a relationship with language ability [70]. A relationship between language and behavioral health psychopathology appears evident in the deaf population.…”
Section: Resultsmentioning
confidence: 99%
“…Deaf female undergraduates are two times as likely to experience interpersonal trauma [31]. Additionally, a community sample of 308 deaf individuals found elevated reports of lifetime emotional abuse (27.5%), physical abuse (21.0%), and sexual violence (20.8%) [32]. Deaf adolescents can experience emotional and behavioral mental health problems associated with low self-esteem and peer rejection [33], and a range of developmental adversities unique to being deaf in a hearing world such as lack of accessible communication with parents and peers [34].…”
Section: Behavioral Healthmentioning
confidence: 99%
“…Physical abuse as a cause of deafness in adults and children is common and should also be screened for. 28 Against a common laypersons' assumption that Deaf people and others with sensory or cognitive impairments do not abuse substances, substance disorders have significant prevalence among Deaf patients (and specialized treatment settings, though limited, exist). 29 Of special note are the physical and neurologic examinations (assessing for asterixis, ataxia, fetor hepaticus, stigmata of chronic liver failure, papillary constriction vs dilation), substance intoxication, and withdrawal syndromes among Deaf patients.…”
Section: What Should the Physical And Neurologic Examination Of A Deamentioning
confidence: 99%